2-(4x+1)=3-(2x-1)

Simple and best practice solution for 2-(4x+1)=3-(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(4x+1)=3-(2x-1) equation:


Simplifying
2 + -1(4x + 1) = 3 + -1(2x + -1)

Reorder the terms:
2 + -1(1 + 4x) = 3 + -1(2x + -1)
2 + (1 * -1 + 4x * -1) = 3 + -1(2x + -1)
2 + (-1 + -4x) = 3 + -1(2x + -1)

Combine like terms: 2 + -1 = 1
1 + -4x = 3 + -1(2x + -1)

Reorder the terms:
1 + -4x = 3 + -1(-1 + 2x)
1 + -4x = 3 + (-1 * -1 + 2x * -1)
1 + -4x = 3 + (1 + -2x)

Combine like terms: 3 + 1 = 4
1 + -4x = 4 + -2x

Solving
1 + -4x = 4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
1 + -4x + 2x = 4 + -2x + 2x

Combine like terms: -4x + 2x = -2x
1 + -2x = 4 + -2x + 2x

Combine like terms: -2x + 2x = 0
1 + -2x = 4 + 0
1 + -2x = 4

Add '-1' to each side of the equation.
1 + -1 + -2x = 4 + -1

Combine like terms: 1 + -1 = 0
0 + -2x = 4 + -1
-2x = 4 + -1

Combine like terms: 4 + -1 = 3
-2x = 3

Divide each side by '-2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 4y+12y=20 | | 75-40m+5m^2= | | 4y+8y=12 | | 44yy=7 | | 4y+4y=16 | | 2x-1+6x=87 | | 3y+6y=9 | | 2x^2-16xy-3x+24y= | | 1c+1a=3 | | (28b-6)-9(3b+2)=-6 | | 30v-60=120 | | 2p^2-20p+48= | | X^2+9xy+14y^2= | | 30v+60=90 | | x^3-2x^2+2x=400 | | 8x+3+5x+8=12x+4 | | 8x+3+5x+8=12+4 | | 2x^4-11x^3+17x^2=0 | | 20c+40=100 | | 3.3x-3=2.3x | | 8x+4=5x+16 | | 4a^2+6a-18=0 | | 2+y=13-3(y+1) | | -15=2x-5 | | 2e+4=6 | | (a+3b)(2a-ab)= | | 35y^2-4y-15=0 | | -(4x-6)+3(2x-4)+3=0 | | 7m+14=21 | | 4x-(4*3x)=4 | | 5n+4=20 | | 10(10+x)=20 |

Equations solver categories